L’Antropocene o il mondo che ha ruotato il suo asse (Altre Modernità, 2019)
The proposed naming of a new geological era, the Anthropocene, has not only enlivened the notoriously placid waters of geology, but has sparked artistic, political, anthropological, historical and philosophical imagination. Global warming challenges the imagination because it tests sensitive perception with its distribution on micro and macro scales in time and space, presenting itself as an accumulation effect and at the same time as geographically scattered. The limits of everyday language are great, despite the literary and poetic efforts to express the unprecedented experience of a nature that has become unnatural, of a world that has rotated on its axis. In question, even before language, is sensitive perception. In a data and visual culture, do the models, the diagrams, the satellite images, the statistics, the "numbers" that flood the media, make us "see" and "feel" something? The visual arts and the exhibitions dedicated in recent years to the Anthropocene have become an important source of experience and knowledge of the phenomena of the climate crisis. They manage to make the invisible visible, to provoke shock by intensifying sensitivity, favoring through an emotional-sensitive experience the knowledge of an elusive reality. The work of the photograph Edward Burtynsky is discussed as a striking example of representation of the Anthropocene.